Distinct phase-selective corrosions of Ti-48Al alloy in aqueous electrolyte and molten salt - Huang, Xiaohu (2024)
Corrosion of Ti-48Al alloys, consisting of γ-TiAl phase and α2-Ti3Al phase in lamellar structures, has been studied by electrochemical method at room temperature and molten salt method at elevated temperatures, respectively. Morphological, crystallographic, and microstructural studies provide direct evidence for γ-phase selective etching by the electrochemical corrosion at room temperature. In contrast, α2-phase selective etching of the Ti-48Al alloy occurred during molten salt corrosion, alongside α2-to-γ phase transformations at elevated temperatures. The distinct corrosion behaviors have been discussed and attributed to different chemical and physical properties between γ-TiAl and α2-Ti3Al phases within the Ti-48Al alloy.